Boosting bio-lipids deoxygenation via tunable metal-support interaction in nickel/ceria-based catalysts. (15th August 2022) - Fu, Lin; Liu, Zhaoxin; Li, Xin; Li, Yongfei; Yang, Houyi; Liu, Yuejin
Graphical abstract: Highlights: Mesoporous Ni/CeO2 -Al2 O3 catalyst with high CeO2 loading (≥20 wt%) was facilely prepared by one-pot EISA method. Well-dispersed CeO2 particles are capable for exposing more oxygen vacancies and switching SMSI from Ni-Al2 O3 to Ni-CeO2 . Increasing CeO2 particles dispersion helps to increase catalyst total acidity and simultaneously decrease catalyst strong acidity. Combining enhanced porosity and tunable SMSI, NiCeAl-EISA catalyst presents excellent resistance to aggregation and coke. NiCeAl-EISA catalyst afforded an n-C11 yield of 98.7%, and remained stable with 92.2% n-C11 yield after 11 consecutive runs. Abstract: Ni-catalysts usually experienced quick deactivation during bio-lipids deoxygenation due to metal sintering and coke. Here we prepared a series of Ni/CeO2 -Al2 O3 catalysts, denoted as NiCeAl-EISA, NiCeAl-WI and NiCeAl-CP, prepared by evaporation-induced self-assembly (EISA), wetness impregnation (WI), co-precipitation (CP) methods, respectively, aiming at tuning metal-support interaction (MSI) in Ni/CeO2 -Al2 O3 catalysts for the deoxygenation of bio-lipids to hydrocarbons. The porosity and surface properties of the catalysts are systematically studied by BET, XRD, H2 -TPR, HR-TEM, FT-IR, O2 -TPD, NH3 -TPD, RPR, Py-FTIR, XPS and in situ XPS. The NiCeAl-EISA catalyst afforded 92.2% n-C11 yield at full methyl laurate conversion, and efficiently deoxygenated different FAMEs, yielding corresponding alkanes yields of 97.8% (n-C9 ), 96.4% (n-C13 ), 94.3% (n-C15 ) and 92.9% (n-C17 ). The TOFs were calculated as 426–719, 241–343 and 148–243 h −1 for NiCeAl-EISA, NiCeAl-WI and NiCeAl-CP catalysts, respectively. Jatropha oil and waste cooking oil were also converted into liquid alkanes (C13-18 ) with a total yield of 95.4% and 93.7%, respectively. The NiCeAl-EISA catalyst exhibits superior catalytic activity and remained stable with 92.2% n-C11 yield after 11 consecutive runs, as compared with NiCeAl-WI and NiCeAl-CP. This significant increase in catalyst activity and stability is closely correlated with the tunable SMSI of Ni/CeO2 -Al2 O3 catalyst, which facilely forms abundant oxygen vacancies and interfacial sites (Ni δ+ -OV -CeOx ). This suppresses strong Ni-Al interaction, thus exposing more active and robust Ni sites to promote R-COOH → R-CHO reduction to produce more alkanes. The weakened Ni-Al interaction also reduces the strong acidity and consequently inhibits the coke formation and simultaneously restrains C–C bond cleavage of hydrocarbons.